1991
DOI: 10.1093/ndt/6.6.428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Biocompatibility During Haemodialysis with Cuprophane and Polacrylonitrile Membranes

Abstract: Clotting within the dialyser is one of the most significant clinical parameters of biocompatibility. A study was designed to evaluate the biocompatibility of two different dialysis membranes (cuprophane and polyacrylonitrile) during therapy with conventional heparin. Transient leukopenia during cuprophane but not during polyacrylonitrile haemodialysis was observed, and elastase release using polyacryonitrile membranes was reduced (P less than 0.001). An elevation in F VIII:C activity during cuprophane haemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…These findings would mean that the stimuli causing the degranulation of platelets persist longer than the stimuli causing the conformational activation of GPIIb/IIIa during hemodialysis. Platelet activation during hemodialysis may be due to many factors, including shear stress, contact activation and agonist activation [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. Further examination is still needed to elucidate the more precise mechanism of platelet activation during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings would mean that the stimuli causing the degranulation of platelets persist longer than the stimuli causing the conformational activation of GPIIb/IIIa during hemodialysis. Platelet activation during hemodialysis may be due to many factors, including shear stress, contact activation and agonist activation [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. Further examination is still needed to elucidate the more precise mechanism of platelet activation during hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…During hemodialysis, the contact of blood with the prosthetic devices and the interaction of blood and artificial membranes result in platelet activation and a decrease in platelet cell count [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. The degree of platelet activation depends on the flow design of the dialysis membrane used [1, 2], the composition and geometry of the dialysis membrane [3, 4, 5, 6, 7, 8, 9, 10], and on rheological factors derived from blood circulation [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipid peroxidation enhances hyperaggregability of platelets [3] that may aggravate dialyser clotting. Clotting within the dialyser is one of the most significant clinical parameters of biocompatibility [4]. Studies have shown that the use of vitamin-E-modified dialysis membranes is associated with a significant reduction in lipoperoxidation and therefore a decrease in oxidative damage compared to conventional membranes [5,6].…”
Section: Introductionmentioning
confidence: 99%